Human hydatidosis in Mar del Plata, Buenos Aires Province, Argentina, (1992-1995): A preliminary study - Elissondo, María Celina (2002)
To assess the health risk associated with Echinococcus granulosus, a retrospective survey of hydatid infection was conducted between 1992 and 1995 by examining records of patients with hydatidosis from two hospitals of Mar del Plata City, General Pueyrredón District, Buenos Aires Province, Argentina.Eighty five patients (34 males and 51 females) with confirm hydatidosis were registered. The average age was 48.2 years. Employee was the occupation that present the greatest percentage of cases (16.5%). Ultrasonography (US) was the most frequently used diagnostic method (28.2%). Infection in the liver occurred most commonly (58.8% of the 85 cases). Of the 85 patients, 74 (87.1%) received surgery; 12 received medical treatment with albendazole.The results obtained in this work from two hospitals show a problematic situation with respect to hydatid disease in Mar del Plata City. To have a good view of infection prevalence in Mar del Plata City, more retrospective survey data on human hydatidosis must be done.